ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP TNGKAT KESEHATAN BANK SYARIAH DENGAN MENGGUNAKAN METODE RGEC PERIODE 2012 - 2016 - Amalia Paramita Sari (Ekonomis: Journal of Economics and Business, 2018)
This study aims to determine how the soundness of the Sharia Bank in the period 2012 - 2016. This type of research is descriptive research with quantitative approach. The variables used were risk profile as measured by the ratio of NPF and FDR, good corporate governance is measured through self-assessment results, profitability as measured by ROA and NIM, and Capital as measured by the ratio of CAR. The data used in this study is secondary data in the form of financial statements of 2012-2016 that have been audited by independent auditors and has been published. This study uses four samples, Bank Muamalat, Bank BRI Syariah, Bank Syariah Mandiri, and Bank BNI Syariah. The results showed that: (1) Variables The magnitude of the effect of NPF, FDR, GCG, ROA, NIM and CAR on bank soundness can be concluded that there are significant influence simultaneously. Independent variable able to explain dependent variable equal to 64%. (2) The variable that has significant partial effect on bank soundness is GCG variable. While the variable of NPF, FDR, ROA, NIM and CAR give insignificant influence to bank soundness. (3) Predicates of bank performance during the period 2012-2016 using RGEC method known to exist 92% of banks indicate that the condition of the bank is stable. This means that commercial banks can be categorized as " soundness" bank.Keywords: Accounting, Health Assessment, Sharia Bank. risk profile, GCG